The Creative Process of Creating Eracycle Dance Works in the Development of the Current Era - Ajeng Ayu Anggerpangestu Anggerpangestu; Nandhang Wisnu Pamenang Nandhang; Jonet Sri Kuncoro (Jurnal Seni Tari, 2025)
The creation of Eracycle dance works is based on the aesthetic spirit of Remo Bolet dance, which is known for being dynamic, expressive, and embodying the value of struggle. This work does not attempt to reconstruct the form of Remo, but rather to transform its principles of energy, feeling, and movement quality into a new language of movement relevant to the development of contemporary performing arts. The method used was qualitative research with data collection techniques through observation, interviews, and literature studies. Data analysis was conducted using a creative process theoretical framework to examine the stages of creation, as well as dance presentation analysis to describe the supporting choreographic and artistic elements. Through a creative process and analysis of dance performances that complement each other, a narrative emerges about the dynamic nature of humans in facing changing times. In conclusion, Eracycle's dance work shows that tradition can serve as an adaptive and relevant source of inspiration in the creation of contemporary dance.